Molekulární demografie medvěda hnědého v Západních Karpatech - Tkáčová, Nikola (Univerzita Karlova, Přírodovědecká fakulta, 2022)
Reliable estimates of population size are an essential tool for effective species conservation and management. The aim of this master thesis was to estimate the census population size and describe genetic variability and structure of the brown bear (Ursus arctos) using non-invasive genetics in Slovakia, which includes the majority of the West Carpathian population. A total of 2,172 samples were obtained during 2019-2021. The majority of the samples were non-invasive, mainly stool samples, which were complemented with tissue samples from roadkills or legally culled animals. Subsequently, DNA was purified and 12 microsatellite loci and the SRY sex marker were amplified. 1036 genotypes were successfully determined, of which 632 were unique. The Slovak population of bears posses a relatively high genetic diversity and similar values of heterozygosity as populations in areas with good state of conservation and relatively intact landscape. Based on Bayesian clustering analysis, population was divided into four clusters, with a certain level of gene flow. Only one cluster was detected in the eastern part of Slovakia (Eastern Carpathians). In the central part of Slovakia (Western Carpathians) all clusters were represented. Observed male to female ratio was 1.006. In males, a higher recapture rate was. Spolehlivé odhady velikosti populace jsou zásadním nástrojem pro efektivní druhovou ochranu a management. Tato práce si kladla za cíl stanovit pomocí neinvazivní genetiky odhad cenzní velikosti populace, genetickou variabilitu a populační strukturu medvěda hnědého (Ursus arctos) na Slovensku, které zahrnuje většinu západokarpatské populace. Během let 2019-2021 bylo získáno celkem 2172 vzorků. Jednalo se zejména o neinvazivní vzorky, především o vzorky trusu, které byly doplněny tkáňovými vzorky. Následně byla izolována DNA a amplifikováno 12 mikrosatelitových lokusů a lokus pro gen SRY jako pohlavní marker. Podařilo se určit 1036 genotypů, z toho 632 unikátních. Slovenská populace má poměrně vysokou genetickou diverzitu ...